Integrated modelling: Coupling of surface evolution and plasma-impurity transport. (December 2020) - Schmid, K.; Effenberg, F.; Dinklage, A.; Rudischhauser, L.; Gao, Y.; Mayer, M.; Brezinsek, S.; Geiger, J.; Fuchert, G.; Miklos, V.; Smith, H.; Turkin, Y.; et al.
Abstract: During the interaction of the scrape off layer (SOL) plasma with the first wall the evolution of both wall and plasma are tightly coupled: The erosion of the first wall leads to an impurity concentration in the plasma which affects the particle and power balance in the plasma. In turn the impurities, when leaving the plasma via transport, can form deposits and mixed materials, far away from their initial source location. These deposits can be eroded, allowing the impurities to stepwise migrate through the fusion device until they end up at a location where the plasma at the wall is cold enough and no further erosion occurs. To describe these processes an integrated model of surface evolution and plasma transport of impurities is needed. The WallDYN code achieves this required coupling of processes by parameterising the output of surface evolution- and plasma impurity-migration-codes by analytical models. For a given fixed background plasma it evolves the surface composition, derives impurity flux into and from the plasma and can from this derive the impurity densities in the plasma. This paper will show the importance of including this recycling of impurities at the wall in impurity migration modelling: The 13 CH 4 seeding experiment performed in the Wendelstein 7-X Stellerator is modelled using the recent extension of the WallDYN code to 3D plasma and wall geometries. A comparison with post mortem analysis of the 13 C deposition shows both qualitative and quantitative agreement with the WallDYN calculations. Graphical abstract: